Interpersonal touch suppresses visual processing of aversive stimuli - Kawamichi, Hiroaki; Kitada, Ryo; Yoshihara, Kazufumi; Takahashi, Haruka K.; Sadato, Norihiro (Frontiers in Human Neuroscience, 2015)
Social contact is essential for survival in human society. A previous study demonstrated that interpersonal contact alleviates pain-related distress by suppressing the activity of its underlying neural network. One explanation for this is that attention is shifted from the cause of distress to interpersonal contact. To test this hypothesis, we conducted a functional MRI (fMRI) study wherein eight pairs of close female friends rated the aversiveness of aversive and non-aversive visual stimuli under two conditions: joining hands either with a rubber model (rubber-hand condition) or with a close friend (human-hand condition). Subsequently, participants rated the overall comfortableness of each condition. The rating result after fMRI indicated that participants experienced greater comfortableness during the human-hand compared to the rubber-hand condition, whereas aversiveness ratings during fMRI were comparable across conditions. The fMRI results showed that the two conditions commonly produced aversive-related activation in both sides of the visual cortex (including V1, V2, and V5). An interaction between aversiveness and hand type showed rubber-hand-specific activation for (aversive > non-aversive) in other visual areas (including V1, V2, V3, and V4v). The effect of interpersonal contact on the processing of aversive stimuli was negatively correlated with the increment of attentional focus to aversiveness measured by a pain-catastrophizing scale. These results suggest that interpersonal touch suppresses the processing of aversive visual stimuli in the occipital cortex. This effect covaried with aversiveness-insensitivity, such that aversive-insensitive individuals might require a lesser degree of attentional capture to aversive-stimulus processing. As joining hands did not influence the subjective ratings of aversiveness, interpersonal touch may operate by redirecting excessive attention away from aversive characteristics of the stimuli.